2016
DOI: 10.1080/1354750x.2016.1252950
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab therapy reverses the increase of allograft inflammatory factor-1 in serum and colonic mucosa of rats with inflammatory bowel disease

Abstract: These findings support AIF-1 as a new biomarker of mucosal healing in experimental colitis and suggest that p38 activation is involved in the mucosal healing intracellular mechanism induced by IFX treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Furthermore, in a study of 47 IBD patients in various stages of disease (e.g. active vs. remission), it was reported that colonic Iba-1 expression was higher in the patients with active disease 33 . There are reports that Iba-1 expression was increased following addition of the pro-inflammatory cytokines IL-1β and TNF-α in a rat macrophage cell line as well as in mice with bleomycin-induced acute lung injury 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study of 47 IBD patients in various stages of disease (e.g. active vs. remission), it was reported that colonic Iba-1 expression was higher in the patients with active disease 33 . There are reports that Iba-1 expression was increased following addition of the pro-inflammatory cytokines IL-1β and TNF-α in a rat macrophage cell line as well as in mice with bleomycin-induced acute lung injury 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the present study is that the potential serum biomarkers (MARCKS, SPINT2, and APOB) of NTDs in the rats were not examined in human maternal serum. Given that there are genetic and environmental differences between animal models and human diseases, while many biomarkers found in animal models have been further confirmed in patients with a variety of different diseases including neurodegenerative, cancer, and inflammatory diseases [36][37][38][39], there are also a few reports that animal biomarkers are not or partly consistent with those in patients [40,41]. Thus, in the future it is necessary to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of rs2857595 gene polymorphism and susceptibility to oral cancer has not been reported, there is a linkage disequilibrium between rs2857595 locus and multiple inflammatory genes (Wei et al, 2014). In addition, a recent animal study found that AIF-1 protein as a biomarker for intestinal mucosal barrier repair can promote intestinal mucosal damage healing by reducing the intestinal mucosal inflammatory response and increasing the differentiation of intestinal mucosal cells (Roman et al, 2017). Although this study only explored the relationship between AIF-1 and intestinal mucosal injury repair, the results suggest that the relationship between AIF-1 gene and oral cancer may be related to the healing of oral mucosal injury, but the specific mechanism remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%